2014
DOI: 10.18632/oncoscience.61
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis, and then stress induced necrosis-like cell death, but not apoptosis, should be the preferred cell death mode for chemotherapy: clearance of a few misconceptions

Abstract: Cell death overarches carcinogenesis and is a center of cancer researches, especially therapy studies. There have been many nomenclatures on cell death, but only three cell death modes are genuine, i.e. apoptosis, necrosis and stress-induced cell death (SICD). Like apoptosis, SICD is programmed. Like necrosis, SICD is a pathological event and may trigger regeneration and scar formation. Therefore, SICD has subtypes of stress-induced apoptosis-like cell death (SIaLCD) and stress-induced necrosis-like cell death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(108 citation statements)
references
References 160 publications
(160 reference statements)
1
106
0
Order By: Relevance
“…For a long time, the belief was that chemotherapy was immunosuppressive by killing immune cells thus having a deleterious effect on immunity to fight the cancer (34,35). However, some chemotherapeutic agents such as taxanes (paclitaxel and docetaxel) have been demonstrated to be immunostimulatory rather than immunosuppressive against tumors, suggesting that other mechanisms than inhibition of cell division may be at play (35,36).…”
Section: The Impact Of Chemotherapy On the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, the belief was that chemotherapy was immunosuppressive by killing immune cells thus having a deleterious effect on immunity to fight the cancer (34,35). However, some chemotherapeutic agents such as taxanes (paclitaxel and docetaxel) have been demonstrated to be immunostimulatory rather than immunosuppressive against tumors, suggesting that other mechanisms than inhibition of cell division may be at play (35,36).…”
Section: The Impact Of Chemotherapy On the Immune Systemmentioning
confidence: 99%
“…However, some chemotherapeutic agents such as taxanes (paclitaxel and docetaxel) have been demonstrated to be immunostimulatory rather than immunosuppressive against tumors, suggesting that other mechanisms than inhibition of cell division may be at play (35,36). In support of these experimental observations, some studies have indicated that advanced breast cancer patients responded to treatment with paclitaxel or docetaxel through an increase of interferon (IFN)-γ, IL-2, IL-6, GM-CSF cytokine levels and enhancement of natural killer (NK) and lymphokineactivated killer (LAK) cell activity in peripheral blood (37).…”
Section: The Impact Of Chemotherapy On the Immune Systemmentioning
confidence: 99%
“…Therefore, IR is unlikely to be due to certain permanent mutations in the genome. Reiterated, it is unlikely that all cells of the body have the same mutations and thus develop IR, not only because mutations occur in a random and stochastic manner but also because many cells can no longer replicate during adulthood and thus cannot fix a mutation in the genome [2,3]. For instance, in the human brain that is 2% of the bodyweight but accounts for 20% of the whole body metabolism [14,15], neurons can no longer replicate in normal adults but manifest evident IR in T2D patients.…”
mentioning
confidence: 99%
“…Actually, for this reason, most classic chemotherapeutic drugs target fast-proliferating cells, and therefore many, but not all, anabolic cells are also those responsible for the common side effects of chemotherapy, including hair loss, low blood cell counts, skin itch, nausea, vomiting, diarrhea, etc. [1,2]. In many cells of the anabolic type, especially in cancer and embryotic cells, glucose is usually metabolized via a so-called glycolysis, in which one glucose molecule is converted to not only two molecules of adenosine-5'-triphosphate (ATP) to provide energy but also two molecules of pyruvate and two molecules of reduced Nicotinamide Adenine Dinucleotide (NADH) that can be used as construction materials for building new cells [32,33].…”
mentioning
confidence: 99%
See 1 more Smart Citation